Do people residing in low socioeconomic areas engage with and benefit from digital mental health services? - Lauren G. Staples; Blake F. Dear; Olav Nielssen; Nickolai Titov (Internet Interventions)
Background: People who are socioeconomically disadvantaged have higher rates of mental disorder and are more likely to face barriers to evidence-based psychological services. Barriers include the cost of treatment, limited availability of local services, and the burden of psychosocial difficulties. Psychological treatment delivered via the internet can overcome some of these barriers. Methods: This study was a retrospective analysis of data collected from 21,561 patients accessing online psychological assessment and treatment. Residential postcodes were used to assign patients to a socioeconomic group (low, mid, or high SES), based on the Index of Economic Resources published by the Australian Bureau of Statistics. Results: The low SES group comprised 34.1 % of the sample and the mid SES group comprised 35.7 %. A perceived lack of local or affordable mental health services was the main reason given for accessing online mental health assessment and treatment. There were small but significant demographic differences between groups at assessment, and baseline symptoms of depression and anxiety were slightly higher for the low and mid SES groups. Despite these differences, there were no group differences in treatment outcomes. All groups showed large symptom reductions on measures of depression (PHQ-9) and anxiety (GAD-7), with Cohen's d effect sizes between 1.36 and 1.47. Reliable deterioration rates were low, and satisfaction rates were high. Conclusion: This study shows that people residing in low socioeconomic areas engage with and benefit from digital mental health services. Results suggest that scalable digital psychological services can improve the equity of access to mental health care.